A Comparative Analysis of Patent Assertion Entities in Markets for Intellectual Property Rights - Steensma, H. Kevin; Chari, Mukund; Heidl, Ralph (Organization Science, 2016)
The patent assertion entity is a relatively new organizational form that neither invents nor commercializes products, but acts as a distributor of intellectual property rights between inventors and commercializing entities. We combine measurement and governance branches of transaction cost theory to compare the efficiency of market intermediation by patent assertion entities to that of bilateral licensing agreements, patent pools, and firm integration. We consider the level of complementarity between patents and the breadth of their commercial applications to develop four general intellectual property configurations that depict distinct relationships between patent supply and patent demand. The costs and benefits of the various governance alternatives are then weighed for each configuration to identify when each alternative is likely to be most efficient. Our analysis suggests that patent assertion entities are most efficient in allocating intellectual property rights when there is substantial patent complementarity such that value is created through patent bundling, and these bundles are applicable across a broad range of product lines such that the costs of measuring infringement and its damages are substantial. We consider how the imperfections of patents as contracts between inventors and society in conjunction with rapid technological evolution contribute to the growth of patent assertion entities. This analysis provides some guidance for managers on how to appropriate value from intellectual property.